Higher platelet reactivity and platelet-monocyte complex formation in Gram-positive sepsis compared to Gram-negative sepsis. (18th August 2017) - Tunjungputri, Rahajeng N.; van de Heijden, Wouter; Urbanus, Rolf T.; de Groot, Philip G.; van der Ven, Andre; de Mast, Quirijn
Abstract: Platelets may play a role in the high risk for vascular complications in Gram-positive sepsis. We compared the platelet reactivity of 15 patients with Gram-positive sepsis, 17 with Gram-negative sepsis and 20 healthy controls using a whole blood flow cytometry-based assay. Patients with Gram-positive sepsis had the highest median fluorescence intensity (MFI) of the platelet membrane expression of P-selectin upon stimulation with high dose adenosine diphosphate (ADP; P = 0.002 vs. Gram-negative and P = 0.005 vs. control groups) and cross-linked collagen-related peptide (CRP-XL; P = 0.02 vs. Gram-negative and P = 0.0001 vs. control groups). The Gram-positive group also demonstrated significantly higher ADP-induced fibrinogen binding ( P = 0.001), as wll as platelet-monocyte complex formation ( P = 0.02), compared to the Gram-negative group and had the highest plasma levels of platelet factor 4, β-thromboglobulin and soluble P-selectin. In contrast, thrombin-antithrombin complex and C-reactive protein levels were comparable in both patient groups. In conclusion, common Gram-positive pathogens induce platelet hyperreactivity, which may contribute to a higher risk for vascular complications